Individual’s Choice on Buying Life Insurance Products in Nepal - Adhikari, Rabina (Nepalese Journal of Finance, 2024)
This study examines the factors influencing individual’s choice on buying life insurance products in Nepal. An individual’s choice on buying life insurance policy is selected as the dependent variable. The independent variables are company loyalty, premium charge, agent, claim settlement and company image. The primary source of data is used to assess the opinions of the respondents regarding individual’s choice on buying insurance products in Nepal. The study is based on primary data with 151 respondents. To achieve the purpose of the study, structured questionnaires is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors driving individual’s choice on buying life insurance products in Nepal.The study showed that company loyalty has a positive impact on individual’s choice on buying life insurance policy. It indicates that company’s loyalty towards consumer stimulates the individual’s choice on buying insurance products in Nepal. Similarly, premium charge has a positive impact on individual’s choice on buying life insurance products. It indicates that fair premium charge stimulates the individual choice. Similarly, agent of the respective company has a positive impact on individual’s choice on buying life insurance products. It indicates that the behaviour and knowledge of agents impulse individuals’ choice on buying life insurance products. The study also showed that claim settlement has a positive impact on individual’s choice. It indicates that proper claim settlement process stimulates the individuals’ choice on buying life insurance products. Furthermore, company image has a positive impact on individual’s choice on buying life insurance policy. It indicates that good company image stimulates individual’s choice on buying life insurance products in Nepal.